Chemistry Central Journal - Berry, R. Stephen; Hii, King Kuok
Chemistry Central Journal publishes peer-reviewed open-access articles in all areas of chemistry. The journal comprises nine subject sections: Analytical Chemistry Biological Chemistry Environmental and Energy Chemistry Food Science Green and Sustainable Chemistry Inorganic Chemistry Materials and Polymers Organic and Medicinal Chemistry                      Physical Chemistry.